Politically correct hate speech - Demenko, Anna; Urbańczyk, Michał (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
In the paper we discuss the reasons behind a specific permissiveness of the Polish judicial authorities with regard to hate speech. Hate speech is criminalized by various provisions of the Polish Criminal Code. But as conducted surveys and statistics show, these regulations do not seem to be used adequately. The acceptance of hate speech does not necessarily result from the fact that we are a less tolerant society, but also to a large extent, from the fact that the scope of what is allowed to be said, especially publicly, is in Poland very broad. Paradoxically, it seems that in this ‘new democracy’ there is more freedom of speech than in Western countries, where political correctness plays a very important role in public and social life. The lack of responsibility that goes with freedom of speech and of boundaries on what might be expressed in public, the scurrilous language used also by high-ranking officials, influence the rules of socially acceptable behaviour. These rules also influence the scope of what is considered criminal behaviour. When tackling the problem of the acceptance of hate speech, it is also very important to remember that legal acts, especially criminal law, might not necessarily be the best way to change the attitudes in a society. Restrictions on freedom of speech might not only have a freezing effect but also be counterproductive – that which it is prohibited to say tends to be said more. The problem is to strike the right balance between those two possible outcomes.